The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0107543
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influence Adherence to Antiretroviral Treatment in an Urban Population, Jakarta, Indonesia

Abstract: IntroductionAlthough the number of people receiving antiretroviral therapy (ART) in Indonesia has increased in recent years, little is known about the specific characteristics affecting adherence in this population. Indonesia is different from most of its neighbors given that it is a geographically and culturally diverse country, with a large Muslim population. We aimed to identify the current rate of adherence and explore factors that influence ART adherence.MethodsData were collected from ART-prescribed outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 21 publications
6
20
2
1
Order By: Relevance
“…In their study, it is likely that their subjects were enrolled in treatment at very high CD4 counts as well as being better prepared in adherence than those of our study. The importance of high adherence to antiretroviral therapy (ART) for HIV disease is well documented, and poor adherence can result in faster disease progression and ADR as well as increased health care costs and sickness., morbidity, mortality, and heightened risk of secondary HIV transmission [52].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, it is likely that their subjects were enrolled in treatment at very high CD4 counts as well as being better prepared in adherence than those of our study. The importance of high adherence to antiretroviral therapy (ART) for HIV disease is well documented, and poor adherence can result in faster disease progression and ADR as well as increased health care costs and sickness., morbidity, mortality, and heightened risk of secondary HIV transmission [52].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have evaluated factors that influence ART utilization in Indonesia [25, 26], and none have done so in prisons where many PLH are diagnosed and given a choice about starting ART. Using a structured questionnaire and in-depth interviews, we therefore undertook and present a mixed method assessment of patient medication attitudes in 102 male PLH recruited from two large prisons in Jakarta.…”
Section: Introductionmentioning
confidence: 99%
“…Counseling has previously been found to improve ART adherence in the hospital's HIV patient population 11 . This study explored factors associated with HIV group counseling attendance and found that a number of demographic and clinical factors impact patient participation.…”
Section: Discussionmentioning
confidence: 99%
“…Having an HIV positive family member may reduce isolation and provide an incentive outside oneself to attend counseling 11 .…”
Section: Discussionmentioning
confidence: 99%